X-ray properties of coronal emission in radio quiet active galactic nuclei - Laha, Sibasish; Ricci, Claudio; Mather, John C.; Behar, Ehud; Gallo, Luigi; Marin, Frederic; Mbarek, Rostom; Hankla, Amelia (Frontiers in Astronomy and Space Sciences, 2025)
Active galactic nuclei (AGN) are powerful sources of panchromatic radiation. All AGN emit in X-rays, contributing around 5%–10% of the AGN bolometric luminosity. The X-ray emitting region, popularly known as the corona, is geometrically and radiatively compact with a size typically ≲10RG (gravitational radii). The rapid and extreme variability in X-rays also suggest that the corona must be a dynamic structure. Decades of X-ray studies have shed much light on the topic, but the nature and origin of AGN corona are still not clearly understood. This is mostly due to the complexities involved in several physical processes at play in the high-gravity, high-density and high-temperature region in the vicinity of the supermassive black hole (SMBH). It is still not clear how exactly the corona is energetically and physically sustained near a SMBH. The ubiquity of coronal emission in AGN points to their fundamental role in black hole accretion processes. In this review we discuss the X-ray observational properties of corona in radio quiet AGN.